Pengaruh Kompetensi Profesional dan Kedisiplinan Guru Terhadap Kinerja Guru pada Madrasah Tsanawiyah di Kecamatan Gantarang Kabupaten Bulukumba - Fatihah, Fatihah; Malik Ibrahim, Misykat; Azisah, St (Manajemen Pendidikan, 2019)
This research aims to analyze the effect of professional competence and teachers? discipline to teachers? performance at Madrasah Tsanawiyah in Gantarang District of Bulukumba Regency, both partial and simultaneously. This research is a quantitative research with the ex post facto method. Respondents in this research are 41 teachers, taken purposive from 196 teachers. The data collection methods used are questionnaire and documentation then analyzed by using regression analysis to examine the hypothesis. The results of this research indicate that: 1) professional competence affect to teachers? performance with relative contribution of 40,2% and effective contribution of 17,2%; 2) teachers? discipline affect to teachers? performance with relative contribution of 59,8% and effective contribution of 25,6%; 3) professional competence and teachers? discipline together affect to teachers? performance with relative contribution of 100% and effective contribution of 42,8%.